PERILAKU SEKSUAL PRANIKAH PELAJAR DI KOTA PEKANBARU (Studi Komparatif Antara Siswa Sekolah Menengah Umum dan Siswa Sekolah Menengah Berbasis Agama Islam) - Putri, Mila Pratiwi Dwi; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted at senior high school based common and senior high school based religion in Pekanbaru, Riau). With a problem that (1) What is factors affect of premarital sexual from students senior high school based common and senior high school based religion, (2) How comparisons of premaritial sexual from senior high school based common and senior high school based religion. This research is comparative research with the quantitative approach and elaboration with narrations descriptive. Population of this research are students grade third, it is 264 students than population was taken with the technique probability sampling, it is sampling propotinal. So, we the sample in this research is 65 students of senior high scool basen common and 55 students of senior high school based religion Islam. To collect data using questioner and documentation. Based on this research there conclusion is factors affect of premarital sexual is (1) Sexul knowledge, (2) Understanding abour religion, (3) there role of family and peers, (4) The sexual passions (5) Source of information (social media). To know of comparing there and nothing between T-test. Finded T-colculated is 2,5 to T in table using standart signification with free degree 118. So, result t0,95(118) = 1,66. If comparate with T result it is large than T-table(t = 2,5 > t 0,95 (118) = 1,66). So, we found significant differences between students senior high school based common and senior high school based religion.Keywords: behavior sexual, comparative, students, premaritial